PENGARUH MEREKaDAN DESAIN KEMASAN TERHADAP KEPUTUSAN PEMBELIAN DEODORANT REXONA DI AIR TAWAR BARAT KOTA PADANG - Muhamad Edo Fernanda, Dra. Jupriani, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
This studymaims to determinemthe effectooof brandssvariables and packaging design on the  purchase decision of the rexona method in Padang City. The population in this study is that all  consumers of dexorant rexona are unknown in number. Thersamples in thisiistudy werehUNP  students of 50 respondents.The data collection technique used in this research is using purposive sampling. Data collection  methods in this study were using questionnaires and interviews. This study uses quantitative  methods, data analysis with descriptive statistics, simple regression, and multiple regression.The results show that on average (1) brand image is in the high category, (2) packaging design is in the high category, (3) purchasing decisions in the category high, (4) there is a brand influence on purchasing decisions as much as 15.7% (r = 0.396 significance of 0.004), (5) there is an influence of packaging design on purchasing decisions of 16.9% (r = 0.411 significance of 0.003), (6) there the influence of brand and packaging design simultaneously on purchasing decisions of 26.8 (r =  0.518 significance of 0.001).Keywords: Brand, Packaging , Purchasing